The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1971
DOI: 10.1111/j.1096-3642.1971.tb00757.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of Hawaiian zoanthids with descriptions of three new species

Abstract: This paper gives descriptions of zoanthids collected from coral reefs and shores of the Hawaiian Islands between June 1965 and June 1967. Isaurus elongatus Verrill (1928) and Palythoa tuberculosa Esper (1791) are redescribed and Zoanthus westitus Verrill (1928) is reclassified as Palythoa westitus. Zoanthus confertus Verrill (1928) and Z. nitidus Verrill (1928) are combined under the new species name Zoanthus pacificus. New species described are P. psammophilia, P. toxica, and Z. kealakekuaensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…Such differences were considered by Muirhead (1989) not to be valid specific characters. Zoanthus coppingeri was described as Z. mantoni by Ryland and Muirhead (1993) and probably also includes Z. pacificus (Walsh and Bowers, 1971). In contrast, the status of Zoanthus vietnamensis is clear, as it shows fixed gene differences at seven loci in comparisons with other Zoanthus samples and is morphologically distinct.…”
Section: Species On the Great Barrier Reefmentioning
confidence: 80%
See 1 more Smart Citation
“…Such differences were considered by Muirhead (1989) not to be valid specific characters. Zoanthus coppingeri was described as Z. mantoni by Ryland and Muirhead (1993) and probably also includes Z. pacificus (Walsh and Bowers, 1971). In contrast, the status of Zoanthus vietnamensis is clear, as it shows fixed gene differences at seven loci in comparisons with other Zoanthus samples and is morphologically distinct.…”
Section: Species On the Great Barrier Reefmentioning
confidence: 80%
“…Of the four families within Zoanthidea, the Zoanthidae are the most ubiquitous and important group on the Great Barrier Reef, and hence the most in need of revision. Sixty species of Zoanthidae are described from the central Indo-west Pacific (Walsh and Bowers 1971) but the true number is unknown. At least 25 are described or reported from the Great Barrier Reef and Torres Strait regions of northeast Australia (Hertwig 1882(Hertwig , 1888Haddon and Shackleton 1891;Saville-Kent 1893;Wilsmore 1909;Carlgren 1937;Ryland and Muirhead 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In Kāneʻohe Bay, Oʻahu, municipal wastewater input at multiple sites caused a shift in benthic community structure during the early 1970’s from corals to filter feeders such as zoanthids, sponges, and barnacles [29, 33, 80]. In the southern part of Kāneʻohe Bay, extensive and persistent beds of zoanthids replaced scleractinian corals on shallow patch and fringing reefs in the 1960s [81]. Although more research is necessary to determine if a link between the Kahului WRF and the adjacent zoanthids exists, the results of these previous studies suggest injected wastewater effluent may support their growth and dominance in Kahului Bay.…”
Section: Discussionmentioning
confidence: 99%
“…of Sphenopus asides from the lack of colonial form and lack of attachment are the same as for Palythoa . In fact, there are some Palythoa species that have somewhat similar ecological features to Sphenopus , such as Palythoa psammophilia Walsh & Bowers, 1971, which inhabits sandy areas with its polyps partially buried (Walsh and Bowers 1971). Other examples are the two new azooxanthellate species in this study with polyps often found in solitary form.…”
Section: Discussionmentioning
confidence: 99%